PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA BAPPEDA PROVINSI SULAWESI TENGAH - Sagita Novyanti, Joyce (Katalogis, 2015)
The Objectives of this research are : (1) to know and analyze effect of job motivation, work environment and job discipline on personnel performance at Regional Develompment Planning Agency, Central Sulawesi Province, (2) to know and analyze effect of job motivation on personnel performance, (3) to know and analyze the effect of work environment on personnel perfomance, (4 ) to know and analyze the effect of job discipline on personnel perfomance. This is a causal descriptive research to investigate the relationship among job motivation, work environment, job discipline, and personnel performance variables involving 169 respondents that have been determined using census method.Â The result of multiple linear regressions show that: (1) job motivation, work environment and job discipline perfoms positive and significant effects on personnel perfomance of Regional Develompment Planning Agency, Central Sulawesi Province, (2) job motivation performs significant effect on personnel perfomance, (3) work environment performs significant effect on personnel perfomance, (4) job discipline performs significant effect on personnel perfomance at Regional Develompment Planning Agency, Central Sulawesi Province